Scalable Synthesis of Amaryllidaceae Isocarbostyril Alkaloids from Enantiomerically Pure 7-Azabicyclo[2.2.1]heptanone Scaffold: Total Synthesis of (+)-7-Deoxypancratistatin - Pandey, Ganesh; Fernandes, Rushil; Dey, Debasis (Synlett, 2018)
A conceptually new and scalable strategy (ten linear steps, 13.9% overall yield) has been developed to synthesize (+)-7-deoxypancratistatin from optically pure 7-azabicyclo[2.2.1]heptanone scaffold. The crucial trans-B–C ring junction was fixed at an early stage of the synthesis by exploiting the rigid bicyclic structural framework of the starting precursor. Stereoselective installation of hydroxyl groups around the perimeter of the cyclohexenyl C-ring involved sequential epoxidation–phenylselenylation–oxydeselenylation sequence followed by dihydroxylation. The most attractive feature of this synthesis is the use of a protection–deprotection step only at the penultimate step making the protocol very efficient and atom economical.
Keywords: asymmetric synthesis; natural products; antitumor agents; total synthesis; alkaloids